Communication structures - Smith, B. W. 1937- (Thomas Telford, 2007)
This work introduces the reader to the basis of design, analysis and construction of lattice towers and guyed masts used for communication purposes. A brief history of tall structures is provided and the various types of structure, dictated by their function and/or location, are described.
Keywords: Antennas (Electronics); Telecommunication -- Equipment and supplies -- Design and construction.; elektronické knihy; electronic books